INDEPENDENSI PENGADILAN PAJAK DITINJAU DARI PASAL 24 AYAT (1) UUD NRI 1945 - Adiel Muhammad Kanantha; Ferry Edwar (Reformasi Hukum Trisakti, 2022)
Number of the Constitutional Court's ruling: 10/PPU-XVIII/2020 This puts the Tax Court's impartiality to the test. The Constitutional Court approved the change made to Law No. 14 of 2002's Article 8 paragraph (2), which now reads, Chairman and Deputy Chairperson are appointed by the President who is elected from and by Judges who are then proposed through the Minister with the Approval of the Chief Justice of the Supreme Court for one term of office. Five years and rejected Law No. 14 of 2002's Article 5 Paragraph 2. The question posed is whether the Tax Court has been independent in exercising its judicial authority and what legal measures might be implemented to ensure the Tax Court's independence. The normative writing approach, the nature of descriptive writing, the type of data using secondary data, qualitative data analysis. As well as drawing conclusions is done with deductive logic. Based on the results of the study, the Tax Court as part of an independent Judicial Power should exercise independent judicial power, but the Tax Court in Law No. 14 of 2002 still places the Tax Court under executive supervision even though it has been tested at the Constitutional Court.